Sclerostin and the regulation of bone formation: Effects in hip osteoarthritis and femoral neck fracture. - Power, J; Poole, K; van Bezooijen, R; Doube, M; Caballero-Alías, A; Lowik, C; Papapoulos, S; Reeve, J; Loveridge, N (2010)
Remodeling imbalance in the elderly femoral neck can result in thin cortices and porosity predisposing to hip fracture. Hip osteoarthritis protects against intracapsular hip fracture. By secreting sclerostin, osteocytes may inhibit Wnt signaling and reduce bone formation by osteoblasts. We hypothesised that differences in osteocytic sclerostin expression might account for differences in osteonal bone-formation activity between controls and subjects with hip fracture or hip osteoarthritis. Using specific antibody staining, we determined the osteocytic expression of sclerostin within osteons of the femoral neck cortex in bone removed from subjects undergoing surgery for hip osteoarthritis (hOA: 5 males, 5 females, 49 to 92 years of age) or hip fracture fixation (FNF: 5 males, 5 females, 73 to 87 years of age) and controls (C: 5 males, 6 females, 61 to 90 years of age). Sclerostin expression and distances of each osteocyte to the canal surface and cement line were assessed for all osteonal osteocytes in 636 unremodeled osteons chosen from fields ( approximately 0.5 mm in diameter) with at least one canal staining for alkaline phosphatase (ALP), a marker of bone formation. In adjacent sections, ALP staining was used to classify basic multicellular unit (BMUs) as quiescent or actively forming bone (ALP(+)). The areal densities of scl(-) and scl(+) osteocytes (number of cells per unit area) in the BMU were inversely correlated and were strong determinants of ALP status in the BMU. In controls and hip fracture patients only, sclerostin-negative osteocytes were closer to osteonal surfaces than positively stained cells. Osteon maturity (progress to closure) was strongly associated with the proportion of osteonal osteocytes expressing sclerostin, and sclerostin expression was the chief determinant of ALP status. hOA patients had 18% fewer osteocytes per unit bone area than controls, fewer osteocytes expressed sclerostin on average than in controls, but wide variation was seen between subjects. Thus, in most hOA patients, there was increased osteonal ALP staining and reduced sclerostin staining of osteocytes. In FNF patients, newly forming osteons were similar in this respect to hOA osteons, but with closure, there was a much sharper reduction in ALP staining that was only partly accounted for by the increased proportions of osteonal osteocytes staining positive for sclerostin. There was no evidence for a greater effect on ALP expression by osteocytes near the osteonal canal. In line with data from blocking antibody experiments, osteonal sclerostin appears to be a strong determinant of whether osteoblasts actively produce bone. In hOA, reduced sclerostin expression likely mediates increased osteoblastic activity in the intracapsular cortex. In FNF, full osteonal closure is postponed, with increased porosity, in part because the proportion of osteocytes expressing sclerostin increases sharply with osteonal maturation.